80 Understanding drinking among emerging adults using the dualistic model of passion: associations with alcohol. (19th September 2017) - Davis, Alan K; Bonar, Erin E; Schneeberger, Diane; Bourque, Carrie; Bohnert, Amy SB; Cunningham, Rebecca M; Walton, Maureen A
Abstract : Statement of purpose: Alcohol misuse (i.e., risky drinking) during emerging adulthood is associated with injury, overdose, and academic and relationship problems. Better understanding of the factors influencing risky drinking could enhance alcohol interventions to reduce injury and other adverse outcomes. In this study, we evaluated whether the variables proposed by the dualistic model of passion (i.e., Obsessive Passion - alcohol use is so compelling that it conflicts with other activities or one's values; and Harmonious Passion - alcohol use is an important but not overwhelming part of one's life), were associated with alcohol consumption, motives, blackouts, and overdose. Methods: Cross-sectional baseline data were analysed, which were collected as part of a larger randomised controlled trial of risky drinkers (i.e., AUDIT-C score >3 females, >4 males) recruited via Facebook advertisements. A canonical correlation analysis was conducted evaluating the dimensional relations between and within sets of independent and dependent variables, while controlling for the intercorrelations among all alcohol variables and sex. Results: The sample (n=109) was mostly female (62%), Caucasian (73%), and young (Mage=22.7, SD=1.1). The first canonical variate indicated that Obsessive Passion was positively associated with frequency of alcohol consumption, binge-drinking, blackouts, and overdose, drinking to cope with negative affect, importance of reducing alcohol use, and was negatively associated with self-efficacy to reduce use. The second canonical variate revealed that Harmonious Passion was unrelated to any negative outcomes, was positively associated with frequency of alcohol use and negatively associated with drinking for conformity reasons. Conclusion: Obsessive, but not Harmonious, passion is associated with several negative alcohol-related outcomes among emerging adults engaged in risky drinking. Future research should examine whether targeting obsessive passion in early interventions reduces consumption, overdose, and blackouts. Significance/contribution: Findings could potentially enhance the efficacy of alcohol interventions among emerging adults engaged in risky drinking.